Expression of Nonmetric Dental Traits in Western European Neanderthals - Frank L'Engle Williams; Rebecca L. George; Marie-Antoinette de Lumley; Gael Becam (Dental Anthropology Association, 2017)
Neanderthals of Western Europe lived across distinct ecogeographic zones from Marine Isotope Stage 7 to 3. Differences in dental morphology from seven Western European sites are compared in terms of ecogeography and chronology. Neanderthals (n = 12) along a north-south gradient were examined. These included the Meuse River Basin of Belgium (Engis 2 and Scladina 1-4A ), Southwest France (Pech de l'Azé 1 and Roc de Marsal), the Pyrenees (Malarnaud and Montmaurin), and the Mediterranean (Hortus). Montmaurin is the oldest, followed by Scladina 1-4A and Malarnaud, whereas the others are younger. Dental casts were prepared from Neanderthal permanent and deciduous dentition. These were described and scored, according to the ASUDAS. Comparisons of dental traits with respect to ecogeographic regions and chronological categories were constructed. Unusual dental features observed include the anterior fovea, entoconulid, metaconulid, and Cara-belli's cusp. Dental traits that distinguish ecogeographic regions are the expression of the M1 hypocone and metaconule, whereas the hypoconulid and Carabelli's cusp separate chronological categories. Differences are present for the entoconulid and metaconulid in both comparisons. Neither chronology nor ecogeography fully explains the results. Similarities in dental traits exist between Roc de Marsal, Pech de l'Azé 1 and Engis 2, and secondarily within the Hortus assemblage.